Candy magazine reshaping teenagers' courtship practices - Engaño, Pamela Mae S.; Macob, Johanne Margarette R.; Menguita, Mae Grace C. (2011)
This study analyzes and determines how forms of print media are capable of influencing their readers. This research discusses how Candy Magazine affects the courtship behavior of its target readers particularly the teenagers.This study considers not just the messages conveyed by the magazine to its readers but also looks at how readers respond to these message about courtship as they are exposed to media almost everyday. Moreover, in this study, the researchers strive to answer what factors trigger teenagers to take the advice presented in the articles of Candy Magazine. To better conduct this research, the researchers use the Elaboration Likelihood Model (ELM) of Richard Petty and John Cacciopo to determine what cognitive process an individual use to evaluate the messages he/she receives. Furthermore, the study also includes Media System Dependency Theory of Sandra Ball-Rokeach and Melvin DeFleur to determine what important factors influence its readers to patronize these reading materials. For this study, the researchers use the qualitative design to determine Candy Magazine's effects on its readers. Furthermore, the researchers also conduct an unstructured interview or an informal conversation interview with eight teenagers who were chosen using snowball sampling -- Author's abstract.
Thesis (Bachelor of Arts in Communication) -- University of the Philippines, 2011.
Includes bibliographical references (leaves 82-85)
Keywords: Candy Magazine; Mass media -- Influence; Courtship -- Philippines; Teenagers -- Attitudes